Asymmetrically substituted calix[4]pyrrole with chiral substituents - Štěpánek, Petr; Šimák, Ondřej; Nováková, Zdena; Wimmer, Zdeněk; Drašar, Pavel (Organic & biomolecular chemistry, 2011)
We have prepared first calix[4]pyrrole containing unprotected carbohydrate moiety directly linked to meso-position of oligopyrrole by stable "C-glycosidic" bond. Basic examination of its superassembly capability is presented.
Keywords: Models, Molecular; molekulární modely; Porphyrins; Calixarenes; Stereoisomerism; kalixareny; porfyriny; stereoizomerie; Molecular Structure; molekulární struktura